Teacher's response to curriculum changes in madrasah learning - Hanafi Pelu; Rosmiati (12 Waiheru, 2023)
This paper aims to explain the teachers’ reaction to curriculum changes in Madrasah learning. The qualitative research method will be applied in this study where researchers will describe data in the form of phrases rather than statistics. While descriptive research is commonly utilized by researchers. Descriptive types only explain phenomena, symptoms, events, and episodes that occur in certain populations or communities. According to the conclusions of this study, learning tools are the compass and forward and backward directions of educational institutions in Indonesia, particularly in Madrasas. Learning tools can be helpful in gaining success and success in implementing learning programs in certain educational units. Looking at the times, compiling a curriculum is not a simple task, but the curriculum is developed based on the needs for the development of a country's educational quality. Furthermore, the curriculum is a notion that must rise to meet all obstacles, yet changes to the curriculum cannot be avoided due to the necessity. Curriculum design is critical because education can meet the requirements of society. As a learning designer, the teacher must begin with a modest and concrete problem, such as the problem of the Madrasah environment. However, the teacher must also think broadly and be visionary. Teachers must remain professional in their tasks even when the curriculum in Indonesia changes, and they must provide a stimulating learning environment so that students feel challenged and like studying.